Comment: The Stock Market: Come Considerations of its Future Structure - Freund, William C. (Journal of Financial and Quantitative Analysis, 1974)
Professor Mendelson's interesting paper reaches one conclusion with which I have no quarrel. Under his “most likely” future scenario, he argues for the need for the individual investor in the stock market to enhance the external equity capital-raising abilities of corporations. However, on the way to that conclusion, he dispenses a number of inconsistencies and confusing points.